Threat to Indonesia’s Constitutional Court Independence Posed by Religious Populist Movements and its Implication Towards Human Rights - Cekli Setya Pratiwi (The Constitutional Court of the Republic of Indonesia, 2024)
One of the biggest challenges to a democratic state under the rule of law today is rising populist movements that endanger the independence of the judiciary. In Indonesia, the religious populist movement led by hardliner Islamic groups continues to try to enter courtrooms to advocate for religious interpretations of court decisions, such as when the Indonesian Constitutional Court reviews the 1965 anti-blasphemy law. This socio-legal research examines empirical data from key resource interviews and secondary data from related Constitutional Court judgements, pertinent legislation, and public policies to determine the socio-political backdrop of the Court decision. This technique enables the author to evaluate religious populism and how it affects Constitutional Court rulings. Political pressure may weaken the court, according to this research, encourage the religious populism of the former of Islamic Defenders Front to impose its will by stating that the repeal of the Anti-Blasphemy Law shows strong indications of corruption within the Court. Religious populism in the justice system raises concerns about political or religious decision-making, thereby undermining the rule of law. This research shows that the pattern or tendency of religious populism shows the Court’s compromise of the legal system towards democratic government in Indonesia, eroding the independence of the judiciary, endangering the right to religious freedom, and weakening public confidence in the justice system and democracy.